Risk Profiles of Emerging and Established Value Chains in Dynamic Markets. Issue 3 (2015) - Koplyay, T.; Mitchell, B.; Cohn, S.; Fekete, M.
Abstract: That supply chain management and logistics are a determining factor for the long term success of a company was well documented by Forrester over a half century ago (Forester, 1958), with the importance of the statement only growing through the intervening years. Whether consciously factored into the operating mode or not, logistics and distribution channel management plays a critical role in the life, and death, of a firm. From the rudimentary beginnings of the start-up company to the hectic world of the growth company and onto the relatively secure existence in mature markets, the value chain consisting of logistics and distribution channel linkages follows the firm, until it solidifies into immutable form of the mature value chain and begins to exert an inexorable pressure on the survival of the entire chain, and conversely the chain imposes its will on the members. The emergence of mature industry value chains is often driven by the need to monopolistically control logistics and distribution channels which provides a competitive advantage but also introduces a serious exposure to pending shock loadings of the chain.